IBNU THUFAIL SEBAGAI MODEL PERADABAN ISLAM - Mubarak, Ahmad Zaki (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2008)
This paper studies one of the ntayor of muslinr philosophy tlrats lbn Thulail, known as Abu Bacer in Latin t-anguagc. According to thc writcr, the illurnination thought of Ibn Thul-ail lourrd on the story of I-layy iltn Yuq:hun at lcast also an exantple ot- knowlcdge thcory. l-hc illuntinalion thoght ollbnLr Thufail was his combination and interection with thc philosophy tradtion in that timc, tlrat tlrc plrilosophical tlrougltt ofAviccnna. So, its unclcrstaltd fiorn thc statement of Ibnu Thu{ail lris sclf that his illunrination thouglrt lound ilr thc story of Ilqtlt illp Yaqzhan is thc explanation ol thc sccrcct of oticntcl plr i losolllry ol Av iccttttc.